Role of Nanotechnology and Their Perspectives in the Treatment of Kidney Diseases - Merlin, J. P. Jose; Li, Xiaogang (Frontiers in Genetics, 2022)
Nanoparticles (NPs) vary by particle size, charge, shape and the density of targeting ligands and are associated with enhancement of the pharmacokinetic properties, targetability, or the bioavailability of drugs. Researchers are now tasked with developing a solution for enhanced renal treatment that is free of side effects and delivers the medicine to the active spot. A growing number of nano-based medication delivery devices are being used to treat renal disorders. Kidney disease management and treatment are currently causing a substantial global burden. Renal problems are multistep processes involving the accumulation of a wide range of molecular and genetic alterations that have been related to a variety of kidney diseases. Renal filtration is a key channel for drug elimination in the kidney, as well as a burgeoning topic of nanomedicine. Although the use of nanotechnology in the treatment of renal illnesses is still in its early phases, it offers a lot of potential. In this review we summarized the properties of the kidney and characteristics of drug delivery systems, which affect a drug's ability to target the kidney and highlights the prospects, opportunities, and challenges.